Allelopathic potential of Tinospora tuberculata as natural herbicide on mustard (Brassica juncea) and sweet corn (Zea mays) - Kamaruzaman, Nurul Ilyana (2015)
Allelopathy is the suppression of growth, development, and distribution of nearby plants and microorganisms caused by the released of toxic compounds called allelochemicals that inhibit the growth of many different plants such as weeds. A study was conducted to determine the allelopathic potential of Tinospora tuberculata on suppression of weeds. Allelopathic potential of aerial parts of Tinospora tuberculata was evaluated on its ability to suppress weeds in two crops, dicotyledon plant, mustard (Brassica juncea) and monocotyledon plant, sweet corn (Zea mays) under glasshouse condition. Dry powders of aerial part (stems and leaves) of T. tuberculata with concentrations of 0g, 10g, 15g and 20g were used as treatments. Species, density, height, fresh weight and dry weight of weeds and height, fresh and dry weight of two crops were measured as indicators of allelopathy of T. tuberculata. Leaves dry powder showed higher inhibitory potential than stem dry powder. Increasing of the dry powder concentration decreased the growth of weeds. The results also suggested that the growth of sweet corn and mustard were may also affected by the concentration of dry powder of T. tuberculata. This suggests that T. tuberculata may possess allelopathic potential and can suppress the growth of weeds as it showed inhibitory activities depend on dry powder concentration.